Updates in Volcanology Linking Active Volcanism and the Geological Record - Németh, Károly (IntechOpen, 2023)
Volcanic geology is a rapidly growing research field within earth sciences. It is a research field that provides the fundamental basic data to be able to reconstruct volcanism that generated eruptive products and the sedimentary processes acted upon to redeposit and rework volcanic pyroclasts. Due to the broad time and spatial scales over which volcanism takes place, it is difficult to determine the correct link between the preserved rocks and the type of volcanism responsible for their formation. Volcanic rocks represent geological processes that occur in a distinct and rapid pattern compared to other geological processes. This book provides insight into the problem of determining the scale of volcanism and linking it to the volcanic rock record. It includes comprehensive reviews and case studies representative of volcanism in diverse geological environments. This book provides a broad overview of the problems, complexity, and usefulness of the active volcanism-based volcanic geology approach to interpreting volcanic rocks in the geological record.